UPAYA MENINGKATKAN HASIL BELAJAR LEMPAR CAKRAM GAYA SAMPING MELALUI METODE PEMBELAJARAN INKLUSI - Asen, Asen; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThe problem in this research was Whether there was an increase in learning outcomes discus throw style side through the method of learning Inclusion in the students of class Vlll SMP of SMP Negeri 1 Balai Kec. Batang Tarang Kab.Sanggau. In accordance with the purpose of research, then this research use type research of â€œClassroom Action Researchâ€. Classroom action research is research done by teachers in the classroom or in the school where he taught with an emphasis on the refinement or improvement of processes and praxis learning. The subject in this research was students class VIII SMP negeri 1 Balai Regency which amounted to 36 people. This research technique using a grating instrument learning outcomes discus throw style to the side. Data analysis using quantitative data. The results of this study showed there was an increase in learning outcomes discus throw style side through the method of learning of inclusion on students of class VIII SMP Negeri 1 Balai. This is evident with the increase of skills of the discus throw style to the side that is good enough on cycle 1 with the average value of the 70,83, while the average value in the second cycle is 79,8.Â Keywords : Discus Throw, Learning Inclusion, Learning Outcomes. Â Â